STRATEGI ADAPTASI PENDIDIKAN DALAM MENGHADAPI DISRUPSI ERA DIGITAL ABAD 21 - Mahfudloh, Elok Thohirotul; Zalfa Ramadani, Labibah Putri; Ali AKbar, Maulana; Ramandani, Nabila; Khobir, Abdul; Kamilia, Nadya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The era of digital disruption in the 21st century has brought fundamental changes to the education system, where technology is no longer just a tool but has become the main driver of changes in the learning paradigm. This research aims to examine educational adaptation strategies in facing the challenges of digital disruption, with a focus on the balance between technological skills and character formation. The research method used is descriptive qualitative with a literature study approach (library research), where data is analyzed from various relevant literature, theories and previous research results. The research results show that an effective educational adaptation strategy involves optimizing educational technology, such as the use of digital libraries and e-learning systems, to encourage students to think critically, creatively and collaboratively. However, it was found that technological adaptation alone was not enough; educational character remains the main pillar for mitigating the negative impacts of easy access to information, such as exposure to negative content. Therefore, educational strategies in the era of disruption must integrate technological innovation with the cultivation of strong personal values. With proper management through policies such as Merdeka Belajar and digitalization of schools, it is hoped that the world of education will be able to produce a generation that is not only digitally proficient but also has good character integrity in facing the dynamics of the 21st century.